PENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATERI MENEMUKAN MAKNA TERSIRAT TEKS MELALUI MEMBACA INTENSIF MODEL JIGSAW DI SEKOLAH DASAR - Tutik Sriyati (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2018)
Abstract : The aims of this research to reveal that through the application of the Jigsaw learning model, there is an increase in student learning outcomes and activities, as well as to measure how much improvement in learning outcomes and learning activities of the material through intensive reading methods on students of class VI. This study is a classroom action research based on the researcher's experience during teaching material; student learning outcomes and activities are always low. The object of this study is the learning outcomes and activity on finding the implied meaning of a text through intensive reading materials while the subject of the study is grade VI students of SD Negeri Sidoharjo 01 UPTD Dikpora Suradadi, Tegal. The data collection method used are the test method, and observation. The test method is used to obtain students' learning outcomes data through the test instrument (evaluation), while the observation method is used to collect students' learning activity data by using observation sheet instrument of student activity where the researcher is assisted by the observer. Student learning outcomes in cycle 1 is 64.83 and at the end of cycle 2 reached 81.03, so it can be concluded that there is an increase of 16.21 points, while student learning activity on cycle 1 is 51.17% and 82.75% in cycle 2, there is an increase of 16.67%. It can be concluded that by implementing Jigsaw model can improve students' learning activities and learning outcomes of Bahasa Indonesia subject so it is expected that teachers can try to apply this learning model and always try to design and implement student-centered learning.